2016
DOI: 10.1177/0033354916662208
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Public Health–Hospital Collaboration in the United States

Abstract: Collaboration refers to relationships in which two or more independent parties voluntarily decide to work together to address a common purpose. Collaborative arrangements take many forms, from informal, nonbinding agreements for information sharing on topics of mutual interest to formal alliances that entail the creation of new organizational entities, substantial financial investments, and long-term legal commitments. In the health field, the spectrum of collaborative endeavors is wide and diverse. An importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Accordingly, we interpreted LHD responses indicating a joint effort for implementing community health needs assessments to be reflective of relatively long-standing relationships (or lack thereof) between an LHD and one or more nonprofit hospitals in a community. While this variable lacked granularity in terms of the nature, strength, and scale of LHD-hospital collaboration (e.g., the content of implementation plans was not known), previous research suggests that any level of meaningful, ongoing collaboration between these two sectors within the same community is uncommon [ 24 ]. Thus, we constructed this variable to measure if such collaboration is associated with positive individual-level health outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we interpreted LHD responses indicating a joint effort for implementing community health needs assessments to be reflective of relatively long-standing relationships (or lack thereof) between an LHD and one or more nonprofit hospitals in a community. While this variable lacked granularity in terms of the nature, strength, and scale of LHD-hospital collaboration (e.g., the content of implementation plans was not known), previous research suggests that any level of meaningful, ongoing collaboration between these two sectors within the same community is uncommon [ 24 ]. Thus, we constructed this variable to measure if such collaboration is associated with positive individual-level health outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence that partnerships may be associated with better health outcomes and LHD performance; [ 33 ] however, robust metrics for studying the strength of LHD partnerships have yet to be developed. Prybil et al recently noted best practices in hospital-public health collaborations, [ 34 ] some of which may be occurring in these positive deviant communities. While some positive deviant jurisdictions in our study may not have a hospital, they may be applying partnership strategies with private providers and community based organizations, leading to exceptional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they recommend that to enable objective, evidence-based evaluation of a partnership’s progress in achieving its mission and goals and to fulfill its accountability to key stakeholders, the partnership’s leadership should specify the community health measures they want to address, the particular objectives and targets they intend to achieve, and the metrics and tools they will use to track and monitor progress. 44 …”
Section: Goals and Objectives Of Population Health Measurementmentioning
confidence: 99%
“…For example, in their analysis of 12 successful partnerships between hospitals and public health, Prybil and colleagues found that these partnerships continue to be challenged in developing objectives and metrics and in demonstrating their linkages with the overall measures of population health on which they have chosen to focus. 9 Thus, the goal of this paper is to summarize the current status of population health measurement and suggest a number of ways to advance the national dialogue on this critical issue. There is no single answer to this question—rather, different measurement approaches are necessary depending on purpose and context.…”
mentioning
confidence: 99%